2017
DOI: 10.1155/2017/8135957
|View full text |Cite
|
Sign up to set email alerts
|

Imaging, Histopathologic, and Treatment Nuances of Pulmonary Carcinosarcoma

Abstract: A 76-year-old female with coronary artery disease, chronic obstructive pulmonary disease, diabetes mellitus type II, and 40 pack-year smoking history presented with a four-day history of cough, productive of green-yellow sputum. Chest X-ray revealed opacification of the left upper lung field, and computed tomography (CT) of the chest showed a large cavitary lesion invading the T2-T3 vertebral bodies, extending into the epidural space, giving rise to mild cord compression. Biopsy of the lesion revealed a poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The most frequent epitheliel component is squamous carcinoma and sarcomatous compenent is rhabdomyosarcoma. Our two patients also had the two components just like the literature [8,10]. In the literature, fewer than 20 cases are reported until 1995 [11][12][13][14].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The most frequent epitheliel component is squamous carcinoma and sarcomatous compenent is rhabdomyosarcoma. Our two patients also had the two components just like the literature [8,10]. In the literature, fewer than 20 cases are reported until 1995 [11][12][13][14].…”
Section: Discussionsupporting
confidence: 71%
“…Xu et al [17] reported 48 cases and this is one of the largest series of the literature. They usually seen an average age of 60-year-old males of heavy smokers [8]. We have two male patients of 58 and 70 year ages and both of them were heavy smokers.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…PSC is an exceedingly rare entity, representing less than 0.5% of all lung cancers [ 2 ]. Gender and heavy smoking are considered risk factors for the development of PSC with a male-to-female ratio of approximately 7:1 and occurring at a median age of 65 years [ 9 ]. The existing literature primarily relies on a limited number of case series and retrospective studies [ 10 ] hence, making it challenging to establish definitive clinical characteristics, diagnosis, treatment strategies, and survival outcomes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%